THE INFLUENCE OF AEROBIC EXERCISE ON STUDENTS FITNESS LEVELS IN SENIOR HIGH SCHOOL 10 BENGKULU CITY - Wisuda Andeka; Lestari Lestari; Reka Lagora (Poltekkes Kemenkes Bengkulu, 2023)
The fitness level of students is not optimal because the physical exercise that is carried out at school is just running around the school field. This research is quantitative research with the Pre Experiment method using the One Group Pretest Posttest design. The sampling technique uses Purposive Sampling of as many as 30 children. The instruments used in this research were the researcher's original type of aerobic exercise with a duration of 30 minutes which was carried out 3 times a week and given for 2 weeks, an exercise observation sheet and the provisions of the Indonesian Physical Fitness Test (TKJI). The results of the study were analyzed univariately and bivariately using the Wilcoxon test. The results showed that the average fitness level of Senior High School 10 Bengkulu City students before doing aerobic exercise was 1.70, after doing aerobic exercise the average increased to 3.70, so there was a difference before and after doing aerobic exercise. Based on the results of the Wilcoxon test, a p-value of 0.000 < 0.005 was obtained, so that it can be concluded that there is a significant influence between aerobic exercise on the fitness level of students at Senior High School 10 Kota Bengkulu. Teachers are expected to improve learning materials that can improve physical fitness so that their physical education learning outcomes also increase and evaluate physical education learning not only limited to cognitive, psychomotor, and affective assessments, but also consider aspects of physical fitness such as gymnastics, jogging, and other physical exercises.